2003
DOI: 10.1152/ajpendo.00355.2002
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine and taurine prevent hyperglycemia-induced insulin resistance in vivo: possible role of oxidative stress

Abstract: -Exposure to high concentrations of glucose and insulin results in insulin resistance of metabolic target tissues, a characteristic feature of type 2 diabetes. High glucose has also been associated with oxidative stress, and increased levels of reactive oxygen species have been proposed to cause insulin resistance. To determine whether oxidative stress contributes to insulin resistance induced by hyperglycemia in vivo, nondiabetic rats were infused with glucose for 6 h to maintain a circulating glucose concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
135
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(141 citation statements)
references
References 88 publications
6
135
0
Order By: Relevance
“…Both NAC and TAU, when given i.v. to rats, prevented hyperglycaemia-induced insulin resistancewhich was also thought to be mediated through oxidative stress-and increases in lipid peroxidation products [22]. In humans, lipid-induced insulin resistance correlated with oxidative stress [32][33][34].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Both NAC and TAU, when given i.v. to rats, prevented hyperglycaemia-induced insulin resistancewhich was also thought to be mediated through oxidative stress-and increases in lipid peroxidation products [22]. In humans, lipid-induced insulin resistance correlated with oxidative stress [32][33][34].…”
Section: Discussionmentioning
confidence: 96%
“…Infusion of the antioxidant N-acetylcysteine (NAC) or taurine (TAU) abolished hyperglycaemia-induced insulin resistance [22]. NAC prevented diabetes in Zucker diabetic fatty rats and ob/ob mice, partly due to its effects on GSIS and preservation of beta cell mass [23].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress and the production of ROS have been strongly implicated as causal in the development of obesitylinked insulin resistance, and a variety of studies have reported that anti-oxidants may have beneficial effects attenuating the characteristics of the metabolic syndrome (3,(35)(36)(37). Increased oxidative stress and production of hydroxyl radicals is linked to the hydroperoxidation of unsaturated acyl chains of membrane lipid and triglyceride.…”
Section: Discussionmentioning
confidence: 99%
“…Saline was given as control (equivolume) because we have shown no difference between saline and BSA infusion using the same experimental protocol (12). NAC was given at 2.14 mol ⅐ kg Ϫ1 ⅐ min Ϫ1 , the dose that reversed insulin resistance induced by glucose in our previous study (30), and at 2.76 mol ⅐ kg Ϫ1 ⅐ min Ϫ1 ; taurine was given at this equimolar dose. Tempol was given at 2.41 mol ⅐ kg Ϫ1 ⅐ min Ϫ1 , the dose that showed protection against ROS toxicity in experimental pancreatitis (31).…”
Section: Studies In Ratsmentioning
confidence: 99%